The Use of Word Clap Game to Improve Students’ Vocabulary Mastery - Meida Kristine Lubis (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2022)
Teaching English vocabulary to Junior High School should be more interesting and joyful. Teachers can use a strategy in conducting materials in order to attract students‟ attention and interest. The objectives of this study are to find out whether “Word Clap Game” can be used as strategy in teaching vocabulary at the eighth grade students of SMP N 1 Tambusai Utara and to find out whether the use of “Word Clap Game” can improve the students‟vocabulary achievement in learning vocabulary. Vocabulary is the one of the English components which has to be mastered and acquired by students in learning a new language. In this study, I used Word Clap Game as a strategy for teaching vocabulary to the eighth grade students of SMP N 1 Tambusai Utara.Word clap game is a game that uses claps and collaboration with other students. An action research was conducted in this study. There were two cycles in this study. Each cycle was carried out through four steps. They were planning, acting, obseving, and reflecting.The subjects of this study were 33 eighth grade students of SMP N 1 Tambusai Utara in the academic year 2021. The writer got the data from observation, test and questionnaire.The writer as a teacher tried to apply word clap game to improve students vocabulary mastery of students. According to the analyses, the pre-test mean is 64,4, while the post-test mean is 77,1. Between pre-test and post-test, they were given one assessment at the end of cycle one with the mean of 69,7. Thus, the students‟ vocabulary mastery is improved by 12,7 (19,7%). The students‟ activity during the treatment shows that they appreciated the Word Clap game I used in the teaching and learning process. Based on the results, it can be concluded that Word Clap game can be used as a strategy to improve the students‟ vocabulary mastery. Moreover,the students‟ opinion about the game also indicates that it helps the students in learning vocabulary.